2022
DOI: 10.1088/2399-7532/ac4c95
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap on soft robotics: multifunctionality, adaptability and growth without borders

Abstract: Soft robotics aims at creating systems with improved performance of movement and adaptability in unknown, challenging, environments and with higher level of safety during interactions with humans. This Roadmap on Soft Robotics covers selected aspects for the design of soft robots significantly linked to the area of multifunctional materials, as these are considered a fundamental component in the design of soft robots for an improvement of their peculiar abilities, such as morphing, adaptivity and growth. The r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 218 publications
2
44
0
Order By: Relevance
“…Further, Mazzolai and others have demonstrated nanosteam generators. [14][15][16] However, in our hands and especially at millimeter scale or above, we found that encasing aqueous droplets in elastomeric polymers such as PDMS led to inconsistent photothermal actuation. This was observed as the droplet heating and spattering into smaller droplets which required time and mechanical agitation to coalesce into a functional droplet again (Fig.…”
Section: Soft Actuationmentioning
confidence: 54%
“…Further, Mazzolai and others have demonstrated nanosteam generators. [14][15][16] However, in our hands and especially at millimeter scale or above, we found that encasing aqueous droplets in elastomeric polymers such as PDMS led to inconsistent photothermal actuation. This was observed as the droplet heating and spattering into smaller droplets which required time and mechanical agitation to coalesce into a functional droplet again (Fig.…”
Section: Soft Actuationmentioning
confidence: 54%
“…Such minimal systems are of interest both in origin of life studies 35 and in growing bottom-up robotics. 36,37…”
Section: Resultsmentioning
confidence: 99%
“…Analyzing biology allows us to develop artificial agents that have similar capabilities [20] and also to understand how EI arises in these beings through 'robo-physics'. There is increasing awareness and acceptance that plants offer and demonstrate many aspect of EI which can provide many insights into EI [21]. Furthermore, their 'brainless' structure still enables computation and intelligence, challenging views and perspective of standard concepts and ideas of intelligence.…”
Section: Current Trends 21 Bio-inspiration and Soft Roboticsmentioning
confidence: 99%